2022
DOI: 10.1002/bit.28233
|View full text |Cite
|
Sign up to set email alerts
|

Pilot scale production and characterization of next generation high molecular weight and tense quaternary state polymerized human hemoglobin

Abstract: Polymerized human hemoglobin (PolyhHb) is being studied as a possible red blood cell (RBC) substitute for use in scenarios where blood is not available. While the oxygen (O2) carrying capacity of PolyhHb makes it appealing as an O2 therapeutic, the commercial PolyhHb PolyHeme® (Northfield Laboratories Inc.) was never approved for clinical use due to the presence of large quantities of low molecular weight (LMW) polymeric hemoglobin (Hb) species (<500 kDa), which have been shown to elicit vasoconstriction, syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Some liposome based HBOCs have been able to nearly match the level of methemoglobin initially after formulation when freshly isolated hemoglobin from expired blood units are used. 21,59 We hypothesize that improved hemoglobin sourcing and timelines can further improve the level of methemoglobin we observe in our system. However, for applications not replacing more than 30% of the blood volume methemoglobin levels of ~20% in HBOCs can be helpful in supporting native red blood cells.…”
Section: Passive Encapsulation Of Functional Human Hemoglobin Maintai...mentioning
confidence: 82%
See 1 more Smart Citation
“…Some liposome based HBOCs have been able to nearly match the level of methemoglobin initially after formulation when freshly isolated hemoglobin from expired blood units are used. 21,59 We hypothesize that improved hemoglobin sourcing and timelines can further improve the level of methemoglobin we observe in our system. However, for applications not replacing more than 30% of the blood volume methemoglobin levels of ~20% in HBOCs can be helpful in supporting native red blood cells.…”
Section: Passive Encapsulation Of Functional Human Hemoglobin Maintai...mentioning
confidence: 82%
“…18 To address these challenges, strategies to increase the molecular diameter of the HBOC and limit free hemoglobin in circulation have become requirements in the design of modern HBOCs. These strategies include chemical crosslinking of hemoglobin, 19,20 polymerization of hemoglobin and crosslinked hemoglobins, [21][22][23] and encapsulation of hemoglobin in liposome and nano-and microparticle systems. 24,25 Liposome encapsulated hemoglobins have demonstrated many of the desired design criteria for an alternative oxygen carrier, including absence of blood group antigens and blood-borne pathogens and a prolonged storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Palmer et al further purified and isolated T-state PolyhHbs by removing cell-free Hb and low-molecular-weight aggregated Hb, which achieved a lower autoxidation rate than previous generations of commercially polymerized HBOCs . This research has been scaled-up on a pilot scale as shown in Figure , which provides a new idea for further designing cross-linked HBOCs based on the allosteric properties of Hb.…”
Section: Hb-based Oxygen Carriersmentioning
confidence: 99%
“…Stage 2 facilitates the exchange of PolyhHb solution with modified Ringer’s lactate solution excipients, removing LMW Hb aggregates (<500 kDa), unmodified cell-free hHb, and free reactants from the final product. Reprinted with permission from ref . Copyright (2022) Wiley.…”
Section: Hb-based Oxygen Carriersmentioning
confidence: 99%
“…[21] To address these challenges, strategies to increase the molecular diameter of the HBOC and limit free hemoglobin in circulation have become requirements in the design of modern HBOCs. These strategies include chemical cross-linking of hemoglobin, [22,23] polymerization of hemoglobins, [24][25][26] and encapsulation of hemoglobin in liposome and nano-and microparticle systems. [27,28] Liposome encapsulated hemoglobin's have demonstrated many of the desired design criteria for an alternative oxygen carrier, including an absence of blood group antigens and blood-borne pathogens, and a prolonged storage capacity.…”
Section: Introductionmentioning
confidence: 99%